Robberies and Some Features of the Methodology of Investigating Robberies - Adnan, Duraković (European Journal of Multidisciplinary Studies, 2018)
Robberies are crimes that particularly negatively and significantly affect the subjective sense of security (but also objective) in society. Special significance of robberies is that they are often on the edge of murder or serious bodily injury. From the criminal law and criminal investigation point of view, robberies range from the so-called "simple" cases in terms of their discovery and clarification to the very serious armed raid on individuals, money transport, legal persons such as banks and other monetary institutions. The suppression of property crimes, especially the part which includes delicts that are carried out using coercion (force and / or threat) like robberies, can be successfully carried out by methods that could be called criminalistic methods. These methods represent a kind of criminalistic engineering - criminal investigation engineering. Criminalistic engineering is all about adjusting criminal investigation tactics, forensic and legal actions and measures to special features of criminal offenses. When carrying out criminal investigation, authorized police officers must constantly take care of the so-called operational criminalistic strategy that rises above the tactical processing of a particular criminal offense, and is aimed at the creation and implementation of a complex of operational-tactical and technical measures and actions with the strategic goal of combating criminality as a whole. This is reflected in the organizational structure of the police and also in the way of criminal control which implies permanent, continuous and systematic penetration and supervision of the so-called the "dark belt" of crime.